The effect of using different diameter lengths of wheat bran Golan 2 on the properties of high-fiber two layer flatbread (bran bread) - محمد رامز; عليو محمود; جمل نورا (Latakia University Journal -Biological Sciences Series, 2022)
The aim of the research is to show how the different measurement of the wheat bran diameters of Golan 2 affects the development of dough containing 50% of them. This research has focused on studying the chemical and physical properties of the bran used, the rheological properties of the dough and the sensory characteristics of the resulting bread. Three different bran diameters (soft bran<500 micrometers, 500 micrometers< medium bran< 1000 micrometers, coarse bran>1000 micrometers) were used to produce high-fiber bran bread. The results of Mixolab showed that the addition of bran led to increase water absorption, and it was noticed that all the lengths of bran diameters used led to a decrease in various mixing properties, gluten quality, starch gelatinization and amylase activity, but improved the freshness properties where delayed retrogradation. In general, the addition of bran reduced the dough’s gas retention, thereby reducing the volume of the loaf, but negatively affected the rheological properties of the dough, the sensory properties of the product. The results also showed that the effect of adding bran depends on the lengths of the bran diameters used, as sensory results showed that the use of soft and medium bran led to good sensory qualities for the resulting bread.